1970
DOI: 10.2135/cropsci1970.0011183x001000060035x
|View full text |Cite
|
Sign up to set email alerts
|

Two Cycles of Directional Selection for Improved Nutritive Value of Alfalfa1

Abstract: A 6‐hour in vitro dry matter disappearance (6H‐DMD) procedure was used to evaluate individual progeny of ‘Vernal’ (Medicago sativa L. and Medicago falcata L.) and ‘DuPuits’ (Medicago sativa L.) clones selected for high or low 6H‐DMD values. Progeny derived from clones with high 6H‐DMD values had consistently higher 6H‐DMD values than progeny from low clones. Additional clones of ‘Culver’ MSA‐C4, MSB‐C4, Medicago glutinosa M.B., and Vernal were screened for high or low 6H‐DMD values over two harvests. Selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…These differences may then become non‐significant. Shenk and Elliot (1970, 1971) showed the high efficiency of clonal selection on a digestibility trait. However, breeding for feeding value must be accompanied by other traits such as forage yield, seed yield, disease and pest resistances, winter resistance, and fall dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may then become non‐significant. Shenk and Elliot (1970, 1971) showed the high efficiency of clonal selection on a digestibility trait. However, breeding for feeding value must be accompanied by other traits such as forage yield, seed yield, disease and pest resistances, winter resistance, and fall dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Rangelander, Spredor 2, and Heinrichs were the most digestible cultivars with high LWR and a high stem IVDMD, whereas Oneida VR had a low plant IVDMD with a low LWR and stem IVDMD, for both spring growth and summer regrowth. Shenk and Elliott (1970) observed that progeny with high DM digestibility were also higher in leaf content. Alfalfa genotypes with high LWR, TN, and IVDMD improve dairy cow performance (Émile et al 1997).…”
Section: Ivdmd and Tn Concentrationsmentioning
confidence: 94%
“…They concluded that selection for low ADF reduced both total cell wall and ADL concentration. Shenk and Elliot (1970) reported that selection for increased digestibility of the whole herbage decreased cell wall constituents and ADL. Kephart et al.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that selection for low ADF reduced both total cell wall and ADL concentration. Shenk and Elliot (1970) reported that selection for increased digestibility of the whole herbage decreased cell wall constituents and ADL. Kephart et al (1989) reported success in selecting for divergent ADL concentration in whole herbage of experimental populations and concluded that many of the differences observed in the divergent ADL lines may have been due to correlated changes in leaf to stem ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation